An Analysis Of The Main Characters In Novel Breaking Dawn By Stephenie Meyer - Fatma Andini; Endang Susilowati (Universitas Ngudi Waluyo, 2024)
This analysis intends to explain about literature which is written in the form of novel. This research analyzes the novel entitled Breaking Dawn by Stephenie Meyer. This novel tells the story of a human who falls in love with a vampire.Bella Swan as the female main character in the novel Breaking Dawn finally married Edward Cullen (Vampire) and then becomes pregnant and has a daughter.The purpose of this research is to analyze the main character in the novelBreaking Dawn.This research method uses descriptive qualitative methods because the data is not numeral but in thefrom of words and sentences. The data of the research is focused on the main characters of the Breaking DawnNovel.The researcher first read the novel Breaking Dawn for several times to get information about the main charactersof the Breaking Dawn novel. Then the researcher collected the data and analyzed them. The research results show that the main roles in the novel are Bella Swan, Edward Cullen, and Jacob Black.They have protagonist and dynamicpersonalities.